2007
DOI: 10.1209/0295-5075/79/50001
|View full text |Cite
|
Sign up to set email alerts
|

True and false forbidden patterns in deterministic and random dynamics

Abstract: In this letter we discuss some properties of order patterns both in deterministic and random orbit generation. As it turns out, the orbits of one-dimensional maps have always forbidden patterns, i.e., order patterns that cannot occur, in contrast with random time series, in which any order pattern appears with probability one. However, finite random sequences may exhibit "false" forbidden patterns with non-vanishing probability. In this case, forbidden patterns decay with the sequence length, thus unveiling th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
216
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(220 citation statements)
references
References 10 publications
4
216
0
Order By: Relevance
“…The NumFW, also known as missing patterns, outperformed SampEn in group differentiation. True missing patterns are robust against noise and they have the potential ability for distinguishing deterministic behavior from randomness in finite time series contaminated with observational white noise [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The NumFW, also known as missing patterns, outperformed SampEn in group differentiation. True missing patterns are robust against noise and they have the potential ability for distinguishing deterministic behavior from randomness in finite time series contaminated with observational white noise [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that the length of time series, N , is constrained as m! ≤ N − (m − 1)τ [17]. Moreover, N >> m!…”
Section: Permutation Entropymentioning
confidence: 96%
“…Statistical methods in order to obtain a model of the mean process have been the classical approach, leading to autoregressive, integrated and moving average models [3]. Characterization of non-linear time series, mainly chaotic, has also attracted the interest of the scientific community [8,9], where phase space reconstruction, spectral analysis or wavelets methods have been revealed to be good indicators of the underlying dynamics of a real time series.Recently the study of the order patterns has been proposed as a technique of evaluating the determinism of a given time series [10,11,12]. Consider a discrete information source emitting a series of observable values [x 1 , x 2 , .…”
mentioning
confidence: 99%
“…Nevertheless, when the series corresponds to a chaotic variable there are some patterns that cannot be encountered in the data due to the underlying deterministic structure: they are the so-called forbidden patterns. It has been demonstrated that most chaotic systems exhibit forbidden patterns, and that in many cases (ergodic finitealphabet information sources) the measure of the number of this patterns is related to other classic metric entropy rates (e.g., the Lyapunov exponent) [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation